Rapid fabrication of three-dimensional gold dendritic nanoforests for visible light-enhanced methanol oxidation. (20th February 2016) - Lin, Chun-Ting; Chang, Mao-Nan; Huang, Hung Ji; Chen, Ching-Hao; Sun, Ru-Jing; Liao, Bo-Huei; Chau, Yuan-Fong Chou; Hsiao, Chien-Nan; Shiao, Ming-Hua; Tseng, Fan-Gang
Abstract: Direct methanol fuel cells (DMFCs) are expected to play a central role in portable power source applications. However, the low efficiency of the methanol oxidation reaction (MOR) has limited their commercial use. To solve this issue, three-dimensional gold dendritic nanoforests (Au DNFs) were prepared to achieve photo-enhanced MOR at the DMFC anode. These approximately 1-μm-thick silicon-supported free-standing nanostructures were fabricated in 5 min under ambient conditions by a facile fluoride-assisted galvanic replacement reaction. Their catalytic performance and photo-enhancement toward MOR were investigated via cyclic voltammetry, chronoamperometry, and electrochemical impedance spectroscopy. Clear catalytic activity enhancement and charge transfer resistance reduction were discovered under illumination. In addition, the chronoamperometric test showed that the oxidation current of MOR was boosted by 28% under broadband illumination. The optimal photoresponse was obtained at 700 nm. These results demonstrate the strong applicability of Au DNFs to photo-electrochemical cells. Furthermore, the fabrication method provides a rapid bottom-up synthetic strategy for silicon-supported free-standing metallic nanostructures.